The Effects of Low Dose Naltrexone on Opioid Induced Hyperalgesia and Fibromyalgia - Jackson, Daniel; Singh, Sunita; Zhang-James, Yanli; Faraone, Stephen; Johnson, Brian (Frontiers in Psychiatry, 2021)
Objectives: While opioids temporarily alleviate pain, the overshoot of balancing pain drivers may increase pain, leading to opioid induced hyperalgesia (OIH). Our goal was to find out what chronic opioid treatment does to pain tolerance as measured by the cold pressor test (CPT), an objective measure of pain tolerance, and to find an alternative effective treatment for chronic pain and FM. Materials and Methods: The setting was an academic addiction medicine service that has an embedded pain service. Patients had routine clinical care starting with an evaluation that included assessment of medical and psychiatric conditions. Participants were 55 patients with OIH and 21 patients with fibromyalgia; all had at least two CPTs. Treatment included a single dose of buprenorphine for detoxification. In this open-label case series, patients were treated with low-dose naltrexone (LDN), a pure opioid receptor antagonist that, we hypothesize, treats OIH and FM by restoring endogenous opioid tone. Results: Comparing initial and last CPT times, those with OIH more than quadrupled their pain tolerance, and those with FM doubled theirs. This improved pain tolerance for OIH and FM was statistically significant (p<0.0001 and p=0.003, respectively) and had a large effect size (r=0.82 and r=0.63, respectively). Discussion: Results suggest that patients on chronic opioid therapy should have pain tolerance measured by CPT with detoxification and LDN provided to correct opioid induced hyperalgesia if found. FM may also be treated with LDN. The main limitation of the findings was lack of a randomized control group treated with placebo. Key Words: Opioid induced hyperalgesia, chronic pain, fibromyalgia, opioid use disorder, low dose naltrexone